2014
DOI: 10.1111/age.12119
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide detection of signatures of selection in Korean Hanwoo cattle

Abstract: The Korean Hanwoo cattle have been intensively selected for production traits, especially high intramuscular fat content. It is believed that ancient crossings between different breeds contributed to forming the Hanwoo, but little is known about the genomic differences and similarities between other cattle breeds and the Hanwoo. In this work, cattle breeds were grouped by origin into four types and used for comparisons: the Europeans (represented by six breeds), zebu (Nelore), African taurine (N'Dama) and Hanw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 61 publications
3
31
0
1
Order By: Relevance
“…() and Porto‐Neto et al . () also performed similar studies, in which similar primary results were observed.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…() and Porto‐Neto et al . () also performed similar studies, in which similar primary results were observed.…”
supporting
confidence: 62%
“…() and Li & Kim () identified significant associations on chromosomes 21 and 26 with growth‐related traits in Brown Hanwoo and Porto‐Neto et al . () identified significant associations on chromosome 21 with immune system traits, we suggest that those associations would also affect Brindle and Jeju Black cattle. Moreover, Lee et al .…”
mentioning
confidence: 62%
“…2015a) are intensively artificially selected for milk yield and milk‐related traits, and the Angus (http://www.dpi.nsw.gov.au/animals-and-livestock/beef-cattle/breeding/beef-cattle-breeds/angus) and Hanwoo (Porto‐Neto et al . ) are selected for meat production and quality traits. It is known that artificial selection for production traits reduce heat tolerance (Belhadj Slimen et al .…”
Section: Resultsmentioning
confidence: 99%
“…However, most of the regions identified in this study were quite long and therefore included many genes. The threshold used in this study to determine significant regions (mean plus two or three SD) via smoothed F ST has been previously recommended by Porto-Neto et al [78]. The high number of genes identified in our study makes it difficult to comment on possible candidate genes.…”
Section: Discussionmentioning
confidence: 99%